From traditional knowledge to novel adaptations of transhumant pastoralists the in face of new challenges in North Patagonia - Easdale, Marcos Horacio; Aguiar, Martín Roberto (Elsevier, 2018)
Transhumant pastoralism is a mobile livelihood strategy in many mountainous, arid and semi-arid regions worldwide. The knowledge of pastoral communities and their lifestyle are strongly rooted in the historical evolution of their own experience in the region, which has largely been part of their social adaptation strategies to environmental variability. However, other recent processes such as urbanization, land-use change, land grabbing and agricultural intensification have promoted the fragmentation of the landscape in this type of regions, thus threatening many mobile farming systems. Our aim was to study the predominant resources and perceptions in the discourse of transhumant pastoralists who are spatially distant from urban areas, with less relative contact with modern lifestyle and consequently, facing certain restrictions on resources availability. The study was oriented to explore the perceptions and adaptations of pastoral families with respect to the problems, challenges, and opportunities that transhumant lifestyle is currently confronting in North-West Patagonia, Argentina. We developed a collective cognitive mapping based on individual semi-structured interviews and network analysis techniques aimed at identifying their predominant perceptions. Traditional cultural issues associated with forms of livelihood and transhumant lifestyle were dominantly manifested, but there were references to some key resources, problems, and opportunities rooted in modern or urban lifestyle system. This mixture of resources and strategies suggests an increasing urban-rural articulation, which is an adaptation to strengthen the current socio-ecological system regime. However, younger generations of transhumant pastoralists are growing in an urban-rural network, which challenges their lifestyles and future developmental pathways.